2007
DOI: 10.1007/s12034-007-0079-5
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and elastic constants of Dharwar cotton fibre using WAXS data

Abstract: Wide-angle X-ray scattering (WAXS) recordings were carried out on raw Dharwar cotton fibres available in Karnataka. Using this data and employing linked atom least squares (LALS) method, we report here the molecular and crystal structure of these cotton fibres. Employing structural data, we have computed elastic moduli tensor components of these fibres. From these investigations, it turns out that the intrinsic strains present in the fibre arise due to hydrogen bonds and not covalent bonds, which is a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…From the Le Bail refinement, the unit-cell parameters were estimated as a = 7.607 Å, b = 10.7441 Å, c = 8.1274 Å, and β = 87.49°, in accordance with literature. 53,54 The presence of silica in the functional textiles is visualized by the decrease of the characteristic peaks of cotton (002), (101) and (110;011) due to the superimposition with the (111) broad peak from the amorphous silica (at 2θ ≈ 22.4°). 55 Taking into account the quantity of silica phase, the amount of nanomaterial incorporated in the hybrid fabrics is in the range of 21À31%.…”
Section: Hydrophobicity and Oleophobicity Properties Of F13-mentioning
confidence: 99%
“…From the Le Bail refinement, the unit-cell parameters were estimated as a = 7.607 Å, b = 10.7441 Å, c = 8.1274 Å, and β = 87.49°, in accordance with literature. 53,54 The presence of silica in the functional textiles is visualized by the decrease of the characteristic peaks of cotton (002), (101) and (110;011) due to the superimposition with the (111) broad peak from the amorphous silica (at 2θ ≈ 22.4°). 55 Taking into account the quantity of silica phase, the amount of nanomaterial incorporated in the hybrid fabrics is in the range of 21À31%.…”
Section: Hydrophobicity and Oleophobicity Properties Of F13-mentioning
confidence: 99%
“…Employing this technique, it is presently conceivable to make a precise atomic model in a unit cell by contributing the mandatory parameters of this sub-atomic structure into the program. For the procedures and methods, we referred to our earlier article [1], the obtained molecular model of Suvin cotton fibre is shown in Fig. 2 and the packing structure along a, b, and c axis are as shown in Fig.…”
Section: Linked Atom Least Squares (Lals) Programmentioning
confidence: 99%
“…It is the ratio of uniaxial stress to the uniaxial strain along a unit vector u [22] and it is the directional dependent and expressed in Fig. 4 for Suvin cotton fibre, where the surface compares to the spherical plot of E(u) acquired from the condition - (1) The maximum and minimum value of Young's modulus represented in Table 5 and is due to the direction compression or tension. Fig.…”
Section: Young's Modulus (E)mentioning
confidence: 99%
See 1 more Smart Citation
“…Further, a number of studies on the crystal and molecular structure of the conventional cotton fibres are being extensively studied and reported by various authors (Abhishek et al 2005;Divakara, Niranjana, & Somashekar, 2009;Samir & Somashekar, 2007a, 2007bSamir, Gopala, & Somashekar, 2007;Samir, Madhu, & Somashekar, 2010). However, we observe that similar studies on the organic cotton fibres are not reported.…”
Section: Introductionmentioning
confidence: 99%